The motivational cost of inequality: opportunity gaps reduce the willingness to work - Gesiarz, F; De Neve, J-E; Sharot, T (Public Library of Science, 2020)
Factors beyond a person’s control, such as demographic characteristics at birth, often influence the availability of rewards an individual can expect for their efforts. We know surprisingly little how such opportunity-gaps impact human motivation. To test this we designed a study in which we arbitrarily varied the reward offered to each participant in a group for performing the same task. Participants then had to decide whether or not they were willing to exert effort to receive their reward. The disparity between offers reduced participants’ motivation to pursue rewards even when their relative position in the distribution was high, despite the decision being of no benefit to others and reducing the reward for oneself. Participants’ feelings partially mediated this relationship. In particular, large disparity was associated with greater unhappiness, which was associated with lower willingness to work – even when controlling for absolute reward and its relative value, both of which also affected decisions to pursue rewards. Our findings suggest opportunity-gaps can trigger psychological dynamics that hurt productivity and well-being of all involved.